THE FACETS OF CREATIVITY ECONOMY (Journal of Economic Research & Business Administration, 2018)
This paper discusses various aspects of so called «creative economy» and «creativity economy», two of many modern concepts characterizing the «new economy» based on knowledge, IC-technologies, creativity and innovation. In this paper, in particular, we conceptually define the «creativity economy» that surpasses an earlier concept of the «creative economy» based, in turn, on the concepts of «creative industries» and «creative occupations»; we also discuss the boundaries of the traditional understanding of «creative economy» based on the industrial and occupational approaches. Some characteristics of «creative industries» in Kazakhstan are also provided. The author concludes that a main defect of the industry and occupation approaches to the understanding and analysis of creative economy is that creativity is considered to relate to some professions, not to people. These approaches reflect the structural economic transformation at the turn of the millennium, but not the qualitative shift in the current economy which depends on and is driven by new ideas in all sectors («mass and constant» creativity). The mass and constant creativity has become the main resource and driver for a new epoch in the economic development, a «creativity economy» that equals neither with the «creative industries» or «creative economy».